KUALITAS BRIKET ARANG DARI BATANG KELAPA SAWIT (Elaeis guineensis Jacq) BERDASARKAN UKURAN SERBUK - Oki Herli Usmayadi; . Nurhaida; Dina Setyawati (Universitas Tanjungpura, 2018)
The research aimed to evaluate the influence of particle size of charcoal from oil palm fronds on the properties of charcoal briquette. The quality of charcoal briquette was evaluated according to Standar Nasional Indonesia (SNI) 01-6235-2000. The methods use Completely Random Design with factor the particle size. The particle size consist of three size, the first particle loss of 10 mesh and retained 20 mesh; the second particle loss of 20 mesh and retained 40 mesh and the third particle loss of 40 mesh and retained 60 mesh. The quality of charcoal consist of moisture content, ash content, fixed carbon, calor value and flying material. The result of research showed that the average value of moisture content was 8.49% - 12.41%, ash content was 7.34% - 8.78%, flying materials was 13.71% - 21.08 %, fixed carbon was 71.57 % - 77.50 % and calor value was 5124 kkal/kg - 5338 kkal/kg. The research result concludes that the best charcoal briquet is on particle size which loss of 10 mesh and retained 20 mesh. This charcoal fulfilled the Indonesian National Standard (INS) 01-6235-2000.Keywords: bioenergy, charcoal briquette, Elaeis guinensis, oil palm frond, particle size